GRADUATES’ EXPECTATION IN RELATION TO THE BIOMEDICINE COURSE AND THEIR INSERTION IN THE LABOR MARKET - Martins Ribeiro, Alessandro; Célia Ferreira Martins, Maria; Goroni Gomes, Thalita (Journal of Interdisciplinary Debates, 2021)
INTRODUCTION: The Biomedical Scientist is prepared for the exercise of numerous activities related to the area, today there are 35 qualifications duly established and regulated by the Federal Council of Biomedicine (CFB) ensuring this performance. Since then the course has expanded and broken national boundaries, so there is also the course in Bahia, especially in the extreme Baiano. MATERIALS AND METHODS: This is a study of perception, carried out with field research with the use of data survey through questionnaires applied to undergraduate students in the year before the SARS-Cov-2 Pandemic. RESULTS AND DISCUSSION: The answers of 63 students were evaluated, and separated according to each question, 33% of the students have the knowledge that for the profession there is still no defined wage cap, needing more regulations with the CFB, 86% of the students did not know that they can act in the Strategy and Health of the Family (ESF), in the vaccination area and acupuncture, at the time to the research 64% of the sample did not exercise paid activity, what facilitates the non-obligatory internship that according to the questioned ones should begin in the 3rd semester. CONCLUSION: Thus, through the study of the students' knowledge of the course, it is clear that health care becomes more complex and the biomedicine student should be trained in a broader way, having contact with discussions in other areas.